Songs in the english class: a strategy to encourage tenth graders' oral production (2006)
This research project examines a strategy in which English songs are used to encourage oral production of tenth graders. It aims at providing a solution to our students’ low speaking proficiency in the English language and to the complexity of working with a large number of students per class. Students involved in this project provided useful data through their participation in activities using English songs. They had the opportunity of speaking in English about their favorite songs; also, we observed that they not only improved their oral production but also showed relaxed, interested and participative attitudes as they worked with songs and particularly when they focused on expressing their ideas freely rather than being concerned about accuracy. Key words: English songs, speaking activities, attitudes, oral production changes Este proyecto de investigación analiza el uso de canciones en inglés como estrategia para fomentar la producción oral en estudiantes de décimo grado. Busca dar una solución al bajo desempeño en la competencia oral en inglés de nuestros estudiantes y a la complejidad del trabajo con grupos numerosos. Los y las estudiantes comprometidos en el proyecto suministraron información útil a través de su participación en las diferentes actividades en las que se usaron canciones en inglés. Ellos tuvieron la oportunidad de hablar en inglés acerca de sus canciones favoritas; también observamos que los estudiantes no sólo mostraron mayor progreso en su producción oral, sino también una actitud relajada, interesada y participativa cuando usamos las canciones y particularmente cuando ellos se concentran más en la libre expresión de ideas que en la manera correcta de decirlas. Palabras claves: Canciones en inglés, actividades de práctica oral, actitudes, cambios en la producción oral